Molecular abundance ratios as a tracer of accelerated collapse in regions of high-mass star formation - Lintott, C; Viti, S; Rawlings, J; Williams, D; Hartquist, T; Caselli, P; Zinchenko, I; Myers, P (Institute of Physics Publishing, 2005)
Recent observations suggest that the behavior of tracer species such as N2H+ and CS is significantly different in regions of high- and low-mass star formation. In the latter, N2H+ is a good tracer of mass, while CS is not. Observations show the reverse to be true in high-mass star formation regions. We use a computational chemical model to show that the abundances of these and other species may be significantly altered by a period of accelerated collapse in high-mass star-forming regions. We suggest that these results provide a potential explanation of the observations, and make predictions for the behavior of other species. © 2005. The American Astronomical Society. All rights reserved.